Assessing population size and structure for Andean Condor Vultur gryphus in Bolivia using a photographic 'capture‐recapture' method. (2nd November 2018) - Méndez, Diego; Marsden, Stuart; Lloyd, Huw
Abstract : The Andean Condor Vultur gryphus is a globally threatened and declining species. Problems of surveying Andean Condor populations using traditional survey methods are particularly acute in Bolivia, largely because only few roosts are known there. However, similar to other vulture species, Andean Condors aggregate at animal carcasses, and are individually recognizable due to unique morphological characteristics (size and shape of male crests and pattern of wing coloration). This provided us with an opportunity to use a capture‐recapture ('sighting‐resighting') modelling framework to estimate the size and structure of an Andean Condor population in Bolivia using photographs of individuals taken at observer‐established feeding stations. Between July and December 2014, 28 feeding stations were established in five different zones throughout the eastern Andean region of Bolivia, where perched and flying Andean Condors were photographed. Between one and 57 (mean = 20.2 ± 14.6 sd) Andean Condors were recorded visiting each feeding station and we were able to identify 456 different individuals, comprising 134 adult males, 40 sub‐adult males, 79 juvenile males, 80 adult females, 30 sub‐adult females and 93 juvenile females. Open population capture‐recapture models produced population estimates ranging from 52 ± 14 (se) individuals to 678 ± 269 individuals across the five zones, giving a total of 1388 ± 413 sd individuals, which is roughly 20% of the estimated Andean Condor global population. Future trials of this method need to consider explicitly knowledge of Andean Condor movements and home‐ranges, habitat preferences when selecting suitable sites as feeding stations, juvenile movements and other behaviours. Sighting‐resighting methods have considerable potential to increase the accuracy of surveys of Andean Condors and other bird species with unique individual morphological characteristics.